TRANSESTERIFIKASI ENZIMATIK ASAM LEMAK DARI SUBSTRAT MINYAK SAWIT DAN SANTAN KELAPA - Joko Sulistyo; Yati Soedaryati Soeka; Rini Handayani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
We have reported he potency of microbial extracellular enzyme for coconut oil by fermentation. Further investigation was aimed to study capacity if the enzyme on bioproses of crude palm oil by transesterification saturated fatty acid to fatty acid ester which is useful for industry of cosmetics, biopharmacy and natural chemistry. We have studied some lipase from culture filtrate of Bacillus subtilis FM-9101, Pseudomonas aerogenes FM-9201, Pseudomonas fluorescens FM-9202, Pseudomonas stutzerri FM 9203, and Candida rugosa FM-9301. Those five strains showed different activities during the hydrolysis substrate which resulted in decreasing or increasing free fatty acids those were liberated from media containing crude palm oil, coconut milk or mixed of both. The optimal transesterification condition were at temperature 45-50o C and pH 4.5 for C. rugosa and pH 6.0 tp 7.0 for P. aerogenes, P. fluorescens, P. stutzeri and B. subtilis. Under the enzyme concentration of 25% (v/v), the transesterification was effectively occurred, while at the concentration of 20% (v/v) the enzymatically biosynthesis required longer incubation period.